Development of Financial Management Information System at Education Foundation Using RAD Method - Denny Jean Cross Sihombing (SEAN Institute, 2023)
Efficient financial management in education foundations is crucial in maintaining the quality of education provided. Lack of transparency in fund management, lack of efficiency in resource allocation, and problems in complying with financial regulations can negatively affect the sustainability of education foundation operations. This research uses the Rapid Application Development Method (RAD) to develop a Financial Management Information System. The research stages included Requirement Definition, Planning, Analysis, Prototyping, Development, Testing, User Evaluation, and Implementation. A total of 30 users, including financial officers from educational foundations, have tested the financial information system. Testing includes testing data accuracy, functionality, integration, performance, security, and user testing. The results of this research include developing a financial information system that successfully meets the foundation's needs. Test users reported a high level of satisfaction with the system, where 87% of users were satisfied, 8% were moderately satisfied, and 5% had some issues that needed to be fixed. This research makes a significant contribution to improving financial management in educational foundations. The developed Financial Management Information System can improve transparency, efficiency, financial monitoring, regulatory compliance, and the quality of education provided by the foundation.